2021
DOI: 10.1021/acs.jcim.0c01420
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Binding Sites on BAX and the Mechanism of BAX Activators through Extensive Molecular Dynamics Simulations

Abstract: The BAX protein is a pro-apoptotic member of the Bcl-2 family, which triggers apoptosis by causing permeabilization of the mitochondrial outer membrane. However, the activation mechanism of BAX is far from being understood. Although a few small-molecule BAX activators have been reported in the literature, their crystal structures in complex with BAX have not been resolved. So far, their binding modes were modeled at most by simple molecular docking efforts. Lack of an in-depth understanding of the activation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…A NMR structure of the latter is also vailable (2LR1 PDB accession number). These findings suggested that the activation mechanism should be considered as a cooperative process in which multiple sites are involved . These results permit us to speculate that the B1 site can play a similar role in Bak, since the structural domains defining the site are similar in both Bak and Bax.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…A NMR structure of the latter is also vailable (2LR1 PDB accession number). These findings suggested that the activation mechanism should be considered as a cooperative process in which multiple sites are involved . These results permit us to speculate that the B1 site can play a similar role in Bak, since the structural domains defining the site are similar in both Bak and Bax.…”
Section: Resultsmentioning
confidence: 67%
“…However, it has been observed that BAM7 and BTSA1 are able to bind to the deep part of the vMIA site in Bax. 22 These two molecules are known Bax activators, although their role in Bax activation also remains unclear. To fully understand the mechanism behind ligand binding to this site in Bax and Bak, additional docking studies and experimental studies need to be performed to better understand a potential allosteric effect of this site.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that there are some well-established computational methods for hotspot searching, such as FTMap , and cosolvent molecular dynamics simulation. FTMap docks small molecular probes onto the target protein to identify the druggable hotspots on the surface efficiently. The cosolvent molecular dynamics, which shares the similar fundamental principles, could simulate the protein system with the probes, allowing one to identify the potential drug binding pockets in a dynamic manner.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al 11 performed extensive MD studies to delineate molecular details of calciuminduced allostery. A cosolvent MD method was employed by Feng et al 12 to detect potential binding sites on the surface of BAX. Chen et al 13 used a randomly accelerated MD algorithm and funnel meta-dynamic simulations to explore the dissociation mechanisms of nonsteroidal GR ligands.…”
mentioning
confidence: 99%